ANALISIS PENERAPAN SANKSI PAJAK BUMI DAN BANGUNAN DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN (PBB) PADA UPTD PENDAPATAN DAERAH KECAMATAN KEDUNGDUNGMADURA PADA TAHUN 2020 – 2023 - Fahroni, Faisal; Wahyudin, Dian (Jurnal Ilmu Administrasi Publik, 2025)
This research was conducted with the aim and purpose of finfing out abaout the application of sanctions for non-complience with paying Land and Building Tax (PBB) for taxpayers registered at the regional reveneu UPTD office, Kedungdung District, Sampang Regency. The tax revenue target always experiences an increase in the state revenue budget every year. Taxpayer data per sub-district that received sanctions mostly increased from year to year. In 2021, the sub-district with the most taxpayers receiving sanctions was Ombul with 95 people. In 2022, the sub-district with the most taxpayers receiving sanctions was Pasarenan with 84 people. In 2023, the sub-district with the most taxpayers receiving sanctions was Ombul with 83 people, and in 2024, the sub-district with the most taxpayers receiving sanctions was Pajeruan with 78 people. In this research, the data collection uses primary and secondary data types whose data collection methods are obtained by interviews, documentation and data analysis. The results of the research is concluded that the application of sanctions for non-complience by taxpayers in paying Land and Building Tax has been implemented in accordance with applicable tax procedures and regulations, howeverthere are several obstacles found in the process of applying sanctions such as invalid taxpayer data,  lack of complience and taxpayer awareness and other obstacles such as economic difficulties or lack of information.